2005
DOI: 10.1158/0008-5472.can-05-1659
|View full text |Cite
|
Sign up to set email alerts
|

Celecoxib and NS-398 Enhance Photodynamic Therapy by Increasing In vitro Apoptosis and Decreasing In vivo Inflammatory and Angiogenic Factors

Abstract: Photodynamic therapy (PDT) elicits both apoptotic and necrotic responses within treated tumors and produces microvascular injury leading to inflammation and hypoxia. PDT also induces expression of angiogenic and survival molecules including vascular endothelial growth factor, cyclooxygenase-2 (COX-2), and matrix metalloproteinases. Adjunctive administration of inhibitors to these molecules improves PDT responsiveness. In the current study, we examined how the combination of PDT and COX-2 inhibitors improve tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
105
3
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(113 citation statements)
references
References 26 publications
4
105
3
1
Order By: Relevance
“…Photofrin–PDT induced the expression of 5 of 140 stress related genes and 1 of the 5 encodes for COX‐2 164. In contrast to the finding from Ferrario et al which demonstrated that combination of COX‐2 inhibitors potentiated PDT responses in vitro,150 addition of COX‐2 inhibitors, NS‐398, rofecoxib or nimesulide before or after PDT did not potentiate PDT responses in C‐26 cells. The COX‐2 inhibitor nimesulid given after, but not before PDT irradiation, significantly enhanced the anti‐tumor efficacy on C‐26 tumor bearing mice, resulting in complete response in the majority of (60% cure) treated mice.…”
Section: Combining Phototherapy With Novel Anti‐cancer Agentscontrasting
confidence: 99%
“…Photofrin–PDT induced the expression of 5 of 140 stress related genes and 1 of the 5 encodes for COX‐2 164. In contrast to the finding from Ferrario et al which demonstrated that combination of COX‐2 inhibitors potentiated PDT responses in vitro,150 addition of COX‐2 inhibitors, NS‐398, rofecoxib or nimesulide before or after PDT did not potentiate PDT responses in C‐26 cells. The COX‐2 inhibitor nimesulid given after, but not before PDT irradiation, significantly enhanced the anti‐tumor efficacy on C‐26 tumor bearing mice, resulting in complete response in the majority of (60% cure) treated mice.…”
Section: Combining Phototherapy With Novel Anti‐cancer Agentscontrasting
confidence: 99%
“…Furthermore, NS398 induced SPARC via down-regulation of DNMT1 and DNMT3b, which is in agreement with a previous study showing a DNMT-dependent increase of SPARC in A549 lung carcinoma cells by NS398 (29). In addition, NS398 has been studied previously for its effect on limiting cell proliferation, angiogenesis, invasion, and metastasis of multiple cancer types (65)(66)(67). It should be noted that NS398 was also shown previously to significantly inhibit bone metastasis of breast cancer cells by suppressing TGF-␤ dependent activation of COX-2.…”
Section: Recurrence Dormancysupporting
confidence: 91%
“…Increased cytotoxicity is reported after dual therapy with PDT and different chemotherapeutic drugs such as cisplatin (Nonaka et al 2002) cyclophosphamide (Casas et al 1998), 5-fluoro-2-deoxyuridine (5FdUr) (Zimmermann et al 2003), metotrexate and doxorubicin (Kirveliene et al 2006). Recently, novel anticancer drugs as TKIs (Dimitroff et al 1999, Liu et al 2007, mAbs (del Carmen et al 2005, Ferrario & Gomer 2006 and COX-2 inhibitors (Ferrario et al 2005) have been reported to enhance PDT-mediated toxicity. However, antagonistic responses have also been reported with PDT in combination with doxorubicin and 5FdUr (Zimmermann et al 2003, Kirveliene et al 2006.…”
Section: Egfr Targeted Drugs; Effects On Pdt and Pci Induced Protein mentioning
confidence: 99%